An Analytical Study on the Electrochemical Behavior and Nucleation Mechanism of a Zn‐Ni Alloy in a Choline Chloride‐Urea Deep Eutectic Solvent. Issue 38 (13th October 2022) - Sun, Haijing; Wang, He; Yang, Shuai; Xaikoua, Souavang; Zhou, Xin; Wang, Baojie; Sun, Jie
Abstract: In this work, the electrochemical behavior and reversibility of electrodeposition of Zn−Ni alloys were investigated by cyclic voltammetry (CV) in the Choline chloride Urea (ChCl‐Urea) system. The results show that the electrodeposition of Zn−Ni alloy follows the normal co‐deposition mechanism and is an irreversible process controlled by diffusion. Timing current method (CA) shows that the electrocrystallization mechanism of Zn−Ni alloy follow three‐dimensional instantaneous nucleation, involving several processes: adsorption process ( jads ), diffusion‐controlled three‐dimensional nucleation/growth process ( j 3D‐DC ), and water reduction process( jWR ). The charge of each process was calculated: Qads, Q 3D‐DC, and QWR, and it was found that changing potential could control the charge contribution rate. According to the kinetic parameters, the number density N0 (cm −2 ) and nucleation rate A (S −1 ) were obtained. According to the best fitting results, Zn−Ni alloy coating was obtained. The microstructure and phase composition of the coating were analyzed by scanning electron microscopy (SEM) and X‐ray diffraction (XRD). Abstract : The electrodeposition of Zn−Ni alloy coating with eutectic flux was studied in detail. Firstly, the deposition mechanism and control process of Zn−Ni were studied. Then, several nucleation processes of Zn−Ni alloy were analyzed and calculated, and according to the best fitting results, Zn−Ni alloy coating was obtained. The results establish the relationship between theoretical calculation and experimental process, and provide valuable ideas for future research.